Government intervention and the resultant sector performance South Africa's diamond industry - Axsel, Kenneth (My University, 2016)
Since the discovery of diamonds in South Africa, Government has played an active role in the establishment of a local processing industry, aimed at the adding of value to locally mined rough diamonds. This study evaluates the influence of Government support and regulation in the performance of South Africa's diamond industry. Statistics were supplied mainly by the South African Diamond Board, the Minerals Bureau and the departments of Finance, and Trade and Industry. Discussions with prominent diamantaires were also undertaken to contrast statutory reporting with informally sourced facis. South Africa's diamond industry undetperforms, particularly the processing industry which benefits from State support at the expense of the other diamond sectors. Government's indirect support of the processing sector cannot be justified in view of its dismal performance. The entire diamond industry should be deregulaled, and State involvement in the processing sector (with special emphasis on the taxation structure) re-evaluated.
A dissertation submitted to the Faculty of Engineering, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science in Engineering. Johannesburg, 1993.
Keywords: Diamond industry and trade--South Africa.; Diamond mines and mining--South Africa.